Pré-visualização de animação tridimensional digital - Arttur Ricardo de Araujo Espindula (2007)
The research on previewing intends to highlight the necessity of theplanning for the digital third dimension animation. It was searched to congregate these plannings in a way to facilitate for the professionals, students, amateurs and the curious ones in this art, the activities that make the process of 3D animation more efficient with basis on getting faster results without having work loss and, if it happens, that it be the small as possible. Knowing that the animation is a slow and expensive process, to be able to study it before applying it improves the possibility of a better exploitation of the material resources, time and available staff. It was pointed concepts and the importance of a work in group where each professional function has to be towards the same final goal, which is the movie making (short or long-film) in the fastest way with the smallest expense as possible sometimes even getting to discard or modifysome scene that comes to present some sort of technical problems or financially high for the production. (Translation for Gabriel Brandão de Oliveira)